The Main Path to C, N, O Elements in Big Bang Nucleosynthesis - 侯素青 吴开谡 陈永寿 舒能川 李志宏 (Chinese physics letters, 2010)
The production of C, N, O elements in a standard big bang nucleosynthesis scenario is investigated. Using the up-to-date data of nuclear reactions in BBN, in particular the ^8Li （n,γ） ^9Li which has been measured in China Institute of Atomic Energy, a full nucleosynthesis network calculation of BBN is carried out. Our calculation results show that the abundance of 12 C is increased for an order of magnitude after addition of the reaction chain ^8Li（n,γ） ^9Li（α,n） ^12B（β） ^12C, which was neglected in previous studies. We find that this sequence provides the main channel to convert the light elements into C, N, O in standard BBN.